Parameters of the 3-minute all-out test: Overestimation of competitive-cyclist time-trial performance in the severe-intensity domain - Nicolò, A.; Bazzucchi, I.; Sacchetti, M. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To verify the accuracy of predicting performance in the severe-intensity domain by means of end-test power output (EP) and the work performed above EP (WEP) obtained from a 3-min all-out test in competitive cyclists.